The industry of idealistic rent-seeking : Agents, captures, and consequences - Bengtsson, Ingemar ; 0000-0002-4284-7686 (RES Working Papers, 2025)
Rent-seeking does not occur in an empty room, rent-seekers act within an institutional framework. Neither does this framework exist in an empty room, it rests on laws and regulations that are the result of action taken by a variety of agents. When one agent takes steps to change the framework to benefit herself, she will also change the conditions for other agents, some for the better and some for the worse. Different rent-seekers may in this way co-operate, intentionally or accidentally. We label this weave of various rent-seekers with various motivations for the rent-seeking industry and sketch a model of how this industry works. We are particularly interested in changes to the institutional framework that facilitates rent-seeking. Who are the key agents in the change of the framework and what are their incentives? We are also interested in those affected, such as businesses subject to regulation that facilitates rent-seeking.
Keywords: Rent-seeking; Bureaucracy; ESG; Public choice